2010
DOI: 10.1615/jenhheattransf.v17.i3.40
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer and Pressure Drop Characteristics of Fin-Tube Heat Exchangers with Different Types of Vortex Generator Configurations

Abstract: A fin-and-tube heat exchanger with three different types of vortex generators is investigated in this study in order to observe the effects of these vortex generators on heat transfer and pressure drop characteristics. The individual as well as the cumulative influences of the vortex generators on the performance of a heat exchanger are examined. The numerical analyses are performed using a computational fluid dynamics (CFD) program named "Fluent". Firstly, each vortex generator type is placed at four differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…At location 3, the flue gas flow area takes its minimum value, so the pressure drop value increase can be explained with this flow area reduction. The results of the present study show a good similarity with the results reported by Bilir et al [26]. They found the best location for different protrusions as the fin tube upper point.…”
Section: The Effect Of Protrusion Location On Finsupporting
confidence: 92%
See 2 more Smart Citations
“…At location 3, the flue gas flow area takes its minimum value, so the pressure drop value increase can be explained with this flow area reduction. The results of the present study show a good similarity with the results reported by Bilir et al [26]. They found the best location for different protrusions as the fin tube upper point.…”
Section: The Effect Of Protrusion Location On Finsupporting
confidence: 92%
“…As can be seen from the literature, there is a great effort made by many researchers in order to obtain more efficient heat exchangers by changing the geometrical parameters of plate fin, fin tube and by placing some types of vortex generators, which will disturb the fluid flow between the channel created by two fins, on the plate fin surface. However, it is also noticed that there is not any study in [26]. The numerical investigation of the mentioned study is enlarged and some other parameters which were not taken into consideration are also included in the present study.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The capacity of heat transfer enhancement of VGs depends on their shape [10,19,22,31,34,37,44] and other parameters such as the angle of attack [1-20, 23, 24, 27, 28, 32, 33, 36, 39, 40], the height of VGs [1-20, 23, 24, 27, 28, 32, 36, 39, 40], the arrangement of VGs [21,25,35,38], the ratio of the size of VGs to the size of the channel [26] and the manufacturing type of VGs (VGs are mounted or punched) [26,27]. According to the reports of Tiggelbeck et al [10], the best performance is given by the delta winglets, closely followed by the rectangular winglets.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental investigations show that the heat transfer characteristics and flow friction are greatly influenced by the fin spacing, size and shape of the fin. Bilir et al [6] investigated effects of vortex generators on heat transfer and pressure drop characteristics on fin-and-tube heat exchanger with three different types of vortex generators. The cumulative effect of vortex generators offers a better heat exchange solution with moderate drop in pressure.…”
Section: Introductionmentioning
confidence: 99%